Optimization of CNG Direct Injector Parameters using model-based calibration framework - Mohamad Hafidzul Rahman, Alias; Mohd Fadzil, Abdul Rahim; Rosli, Abu Bakar (Springer, 2021)
This paper presents an optimization study conducted based on a direct injector model running on compressed natural gas. The purpose of the study is to identify the optimal setup for the selected input parameters which deliver maximum injection quantity at the lowest solenoid current. The optimized injector input parameters were the injection pressure, injection duration, and input voltage. The optimization study was conducted using MATLAB’s Simulink, Model-Based Calibration (MBC) Toolbox and injector test rig. The optimization data is generated by a validated, zero-dimensional, first principle injector model. The optimize calibration results were implemented in the injector experiment for verification. It was found that the simulation result of the mass flow rate for baseline versus optimization shows an increment of 15.64%. In comparison, the experimental result for baseline versus optimization shows an increase of 35.79%. Additionally, a comparison between the baseline work for simulation versus experiment produced RMSE of 0.2467 while the optimization work for simulation versus the experiment provides an RMSE value of 0.1860.